Tourist satisfaction index: a preliminary case study on Cameron Highlands, Pahang / Zarul Azhar Nasir, Ahmad Ashaari Alias and Mohd Fauzi Mohd Harun - Nasir, Zarul Azhar; Alias, Ahmad Ashaari; Mohd Harun, Mohd Fauzi (Research Management Institute (RMI), 2013)
This study aims to assess the determining factors that influence tourists' satisfaction and to estimate the tourist satisfaction index in Cameron Highlands, Pahang, a tourism destination in Malaysia. To meet the objectives of this study, a set of questionnaire was used as an instrument to collect the primary data from tourists visiting Cameron Highlands. The questionnaire consists of 7 categories and 34 items pertaining to services provided in Cameron Highlands and tourist's impression of Cameron Highlands as a tourism destination. The 7 service categories were i) cleanliness, ii) natural surroundings, iii) recreational activities, iv) support facilities and infrastructure, v) information, vi) public transportation, and vii) security level. Information on specific and general satisfaction levels with regard to each item and socio-demographic profiles of tourists were also collected. Data were analysed using the Statistical Package for Social Sciences (SPSS) 20.0. The result shows that the most highly satisfied factors in determining tourist satisfaction level is natural surroundings (5.315); followed by recreational activities (5.055), security level (4.795), information (4.760), support facilities and infrastructure (4.685), public transportation (4.595) and cleanliness and hygiene (4.375). With respect to the satisfaction index, this study has found that the index is at 76.34 percent which can be regarded as a moderate level.